ANALISIS KELAYAKAN USAHATANI JAGUNG HIBRIDA PADA LAHAN KERING DI MERAUKE, PAPUA - Frans Palobo; Herman Masbaitubun; Siska Tijaroh (Universitas Sebelas Maret, 2019)
The success of agricultural development is very closely related to the technology used in farming. Good technology is technology that is compatible with climate, variety, farming systems and adaptive. Corn commodities are still the second strategic commodity after rice because in some regions, corn is still the second staple food after rice and also contributes to animal feed. This study aims to determine the economic feasibility level of corn farming in dry land through the application of technological innovations for the use of seeds of new improved varieties of hybrid corn. The study was conducted in Jagebob District Kartini District, Merauke Regency, from August to December 2017, the method of approach which was conducted on-farm and off-farm with treatment (1) use of 4 (four) Bima Hybrid varieties 19 URIs, Bima 20 URIs, Nasa 29 and Bisi-2, (2) analyze the income of corn farming using an analysis of the balance of revenues and costs. The results of the study showed that the treatment of varieties of income of hybrid corn farming Bima 19 URI varieties; R / C 2.25, B / C 1.25, TIP 296 kg / ha, TIH Rp 2,273 / kg and employee benefits Rp 237,233 / day; Bima 20 URI varieties and Nasa-29 varieties R / C value 3.18 ,. B / C 2.18 TIP 249 kg / ha, TIH Rp. 1,783 / kg and employee benefits Rp.420,767 / day. Whereas Bisi-2 varieties; R / C 2.87 ,. B / C 1.87, TIP 260 kg / ha, TIH Rp. 1,783 / kg and employee benefits Rp.360,422 / day.